Instructional design case studies in communities of practice - Keppell, Michael J. 1961-. (Hershey, PA Information Science Pub., 2007)
"This book explains the strategies and heuristics used by instructional designers when working in different settings, articulates the sophistication of communication strategies when working with subject matter experts, and provides insight into the range of knowledge, skills, and personal characteristics required to complete the tasks expected of them"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Instructional systems -- Design -- Case studies